rDNA loci and heterochromatin positions support a distinct genome type for ‘x = 9 species’ of section arachis (arachis, leguminosae) - Silvestri, María Celeste (2014)
Fil: Silvestri, María Celeste. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.